Persepsi Mahasiswa Program Studi Komunikasi dan Penyiaran Islam dalam Pesan Dakwah Kitab Ihya’ Ulumuddin Oleh KH. Abdul Ghofur - Mochamad Refi; Ainur Rofiq (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2020)
The recitation of the Ihya' Ulumuddin book which is always taught to students and the general public is still not fully expected by caregivers, as is the lack of maximum and consistent student participation in studying the Ihya' Ulumuddin book due to various influencing factors, and also the lack of knowledge of students with da'wah messages and about mastery of religious knowledge so that when recitation encountered problems in the study of the book of Ihya 'Ulumuddin. The formulation of the problem in this study, namely: How are the Perceptions of Students of the Islamic Communication and Broadcasting Study Program in the Study of the Book of Ihya 'Ulumuddin by KH. Abdul Ghofur at Sunan Drajat Islamic Boarding School Lamongan? How is the message of Da'wah from the Book of Ihya 'Ulumuddin by KH. Abdul Ghofur at the Sunan Drajat Islamic Boarding School Lamongan. The purpose of this study was to determine the perceptions of students of the Islamic Communication and Broadcasting Study Program in the Message of Da'wah Kitab Ihya 'Ulumuddin by KH. Abdul Ghofur at the Sunan Drajat Islamic Boarding School Lamongan. The results showed that: (1) Perceptions of students of the Islamic Communication and Broadcasting Study Program in the study of the book Ihya 'Ulumuddin by KH. Abdul Ghofur very interesting delivery, clear, and easy to understand. Very experienced and very detailed when delivering da'wah messages through the Ihya 'Ulumuddin book so that it is easy to understand by the general public, can attract students or the public to attend the recitation and be enthusiastic in listening to the Ihya' Ulumuddin book recitation directly. 2) The message of the da'wah book of Ihya' Ulumuddin which is interesting in the study of Hikmah Modok, one hour of boarding is the same as wiridan one year, referring to students' understanding of the message of da'wah so they want to learn to try hard in learning religious knowledge by understanding the message of da'wah about life in the world. In this world, the message of da'wah is about establishing friendships, forming good personalities and morals, so that they can make students and the public better learn the teachings of Islam.